Cerebral and splanchnic oxygenation during automated control of inspired oxygen (FiO2) in preterm infants. Issue 7 (26th March 2021) - Dani, Carlo; Pratesi, Simone; Luzzati, Michele; Petrolini, Chiara; Montano, Simona; Remaschi, Giulia; Coviello, Caterina
Abstract: Objectives: Our aim in this study was to assess the effect of the Predictive Intelligent Control of Oxygenation (PRICO ® ) system on cerebral (rSO2 C) and splanchnic (rSO2 S) oxygenation in a cohort of preterm infants with frequent desaturations. Methods: Twenty infants with gestational age <32 weeks ( n  = 20) were assigned in random sequence to 12 h of automated or manual adjustment of FiO2 . Over this period, they were studied continuously by near‐infrared spectroscopy (NIRS). Results: We found that rSO2 C [68.0% (60.5%–74.7%) vs. 68.5% (62%–72%); p  = .824] and rSO2 S [27.0% (17.3%–45.7%) vs. 27.0% (15%–53%); p  = .878] were similar during automatic and manual control of FiO2 . Time spent with SpO2 90%–95% was higher during the automatic than manual control of FiO2, while time spent with SpO2 <80% or >95% was lower. Conclusions: Automated control of FiO2 with PRICO ® system did not improve brain and splanchnic oxygenation in comparison with manual control in a cohort of preterm infants, but it significantly decreased SpO2 fluctuations and limited the duration of both hypoxemia and hyperoxemia.